2017
DOI: 10.1007/s10961-017-9565-0
|View full text |Cite
|
Sign up to set email alerts
|

Have you been served? The impact of university entrepreneurial support on start-ups’ network formation

Abstract: University-based entrepreneurial support organizations devote increasing efforts to create a context and opportunities for interaction among start-up firms. The basic assumption behind these efforts is that networks facilitate access to knowledge and resources and increase the chances of success for start-ups.However, the mechanisms that facilitate the creation of business ties with other members of the same community are yet to be identified and empirically tested. This paper leverages the social network and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 77 publications
0
28
0
2
Order By: Relevance
“…Fichter and Tiemman [7] and Paniccia and Biaocco [6] found that TTOs constitute appropriate mechanisms for the transmission and materialization of a culture oriented towards the commercialization of social innovation. On the other hand, several authors state that TTOs develop additional support functions for ASOs that may contribute towards the development of innovations, in general, and social innovations in particular [7,86]. First, prior research has shown that TTOs are sources of supportive activities such as consultancy services, management training, administrative and legal tasks, and human resource services that facilitate the development of ASOs [95,[112][113][114].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fichter and Tiemman [7] and Paniccia and Biaocco [6] found that TTOs constitute appropriate mechanisms for the transmission and materialization of a culture oriented towards the commercialization of social innovation. On the other hand, several authors state that TTOs develop additional support functions for ASOs that may contribute towards the development of innovations, in general, and social innovations in particular [7,86]. First, prior research has shown that TTOs are sources of supportive activities such as consultancy services, management training, administrative and legal tasks, and human resource services that facilitate the development of ASOs [95,[112][113][114].…”
Section: Discussionmentioning
confidence: 99%
“…This increasing awareness towards sustainability is reflected in their strategic plans that include new goals, visions, and priority areas related to corporate social responsibility [7]. By taking these strategic plans as a reference, universities integrate this social and sustainable culture within the university community through their teaching, research, and entrepreneurship activities and nurture ASOs with this culture [85,86]. In this respect, Fitcher and Tiemann [7] found that universities include specific aspects related to sustainability and solutions to social problems within their teaching programs and are interested in designing funding programs to support research projects linked to corporate social responsibility.…”
Section: Institutional Context Of the Entrepreneurial Ecosystemmentioning
confidence: 99%
See 2 more Smart Citations
“…Against this background, start-up incubators and accelerators have been established as instruments to foster student entrepreneurship and university spin-off activities (Bliemel, Flores, De Klerk, & Miles, 2019;Breznitz, Clayton, Defazio, & Isett, 2018;Wright, Siegel, & Mustar, 2017) thus creating additional complements in knowledgeintensive entrepreneurial ecosystems (Malecki, 2018;Mason & Brown, 2014;Pitelis, 2012;Spigel, 2017;Stam, 2015). In this line of thinking, Open Creative Labs are complements within a wider network of financial, social, and material resources for (maker) entrepreneurs who organize the production, marketing, and sales of their products without the organizational setting of a firm (Doussard et al, 2018).…”
Section: Spatial Perspectivesmentioning
confidence: 99%